Financial development, international trade and economic growth: Empirical evidence from Pakistan - Safana Shaheen; Masood Sarwar Awan; Muhammad Waqas; Muhammad Amir Aslam (Romanian Journal of Fiscal Policy (RJFP), 2011)
The study utilizes the Autoregressive-distributed lag (ARDL) approach for cointegration and Granger causality test, to explore the long run equilibrium relationship and the possible direction of causality between international trade, financial development and economic growth for the Pakistan economy. Imports plus exports of goods and services is used as a proxy for international trade, while broad money (M2) and gross domestic product (GDP) are used as the proxies for financial development and economic growth, respectively. Result explores a long run relationship between the variables. In case of Pakistan, economy supply leading hypothesis is accepted. Moreover, unidirectional causality is observed from international trade to economic growth and from financial development to international trade.
Keywords: F4; F13; G18; F02; 330; financial development; international trade; economic growth; Pakistan